New cases of social parasitism among pseudoscorpions from Colombian populations. Issue 4 (1st October 2016) - Lacava, M.; González-Gómez, J.C.; Valenzuela-Rojas, J.C.; Moncayo, C.; Cardozo, L.; Tizo-Pedroso, E.; García, L.F.
Abstract : Social parasitism is more commonly found among the Hymenoptera. However, a recent study reported a case of parasitism between Neotropical pseudoscorpion species. Here, we extend the knowledge about this relationship, adding information about the species from Colombia. Sampling of Paratemnoides nidificator colonies in a secondary dry forest revealed the presence of two other species of pseudoscorpions also sharing the nest of the host. We presented data about the occurrence of Parachernes melanopygus and a second inquiline species of genus Lustrochernes (both Chernetidae) and how they affect the host species. Aspects of the species ecology and behaviour are discussed.